2019
DOI: 10.1007/s40071-019-00242-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nile tilapia in monoculture and polyculture with giant freshwater prawn in biofloc technology system and in recirculation aquaculture system

Abstract: Biofloc technology system (BFT), recirculation aquaculture system (RAS) and polyculture promote efficient use of water, area and nutrient recycling, which are essential practices for sustainable aquaculture development. The aim of this study was to evaluate the growth, feed efficiency, biofloc composition and water quality of Nile tilapia Oreochromis niloticus (Linnaeus, 1758) in monoculture and polyculture with giant freshwater prawn Macrobrachium rosenbergii (De Man, 1906) in BFT and RAS, over a period of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Control can be more challenging due to dependent factors such as feed levels, which will be related to stocking density and dissolved oxygen levels (Boyd et al ., 2020). Controlling water quality traditionally requires technical solutions such as thermoregulation, water exchange, aeration, mechanical technology, and biofiltration or biofloc technology (Martins et al ., 2010; Hisano et al ., 2019). However, polyculture systems can offset some of these control requirements via internal regulatory processes such as recycling of the nutrients in waste (Neori et al ., 2004; Martinez‐Porchas et al ., 2010; Boyd et al ., 2020).…”
Section: Limits Of Polyculture Approaches and Future Developmentsmentioning
confidence: 99%
“…Control can be more challenging due to dependent factors such as feed levels, which will be related to stocking density and dissolved oxygen levels (Boyd et al ., 2020). Controlling water quality traditionally requires technical solutions such as thermoregulation, water exchange, aeration, mechanical technology, and biofiltration or biofloc technology (Martins et al ., 2010; Hisano et al ., 2019). However, polyculture systems can offset some of these control requirements via internal regulatory processes such as recycling of the nutrients in waste (Neori et al ., 2004; Martinez‐Porchas et al ., 2010; Boyd et al ., 2020).…”
Section: Limits Of Polyculture Approaches and Future Developmentsmentioning
confidence: 99%
“…In another study, the performance of the BFT versus the RAS on Nile tilapia, Oreochromis niloticus in monoculture and polyculture with giant freshwater prawn, Macrobrachium rosenbergii was evaluated. It was reported that the BFT offers better growth performance for O. niloticus in monoculture and in polyculture with M. rosenbergii compared to RAS ( Hisano et al 2019 ).Thus, both RAS and BFT systems play a significant role optimizing the growth performance of aquatic animals resulting in the reduction of their production expenses ( Fleckenstein et al 2018 ). Nevertheless, fossil fuel-based RAS increases both the operational cost and the bad environmental impact because of its high energy requirements ( Badiola et al 2018 ).…”
Section: Biofloc Is a Significant Food Source In The Recirculating Aqmentioning
confidence: 99%
“…To reduce the damage, water with high nitrogen concentration would be directly discharged, which results in the eutrophication of ambient water bodies (Dauda et al, 2019; Thomsen et al, 2020). Biofloc technology (BFT) is very attractive for reducing inorganic nitrogen due to low cost and energy consumption, enhancing the assimilation of ammonium through the addition of carbon sources, to form biofloc that consists of algae, microorganisms, protozoa and particulate organic matter with zero or low water exchange rates (Avnimelech, 1999; Badiola et al, 2018; Hisano et al, 2019). In consideration of cost and availability, the most frequently used carbon sources are starch, sucrose, glucose, glycerol, molasses, flour and bran (Dauda, 2020; Wei et al, 2016), and Luo et al (2020) suggested insoluble biodegradable polymers such as poly‐β‐hydroxybutyric (PHB), polycaprolactone (PCL) and polybutylene succinate (PBS) as carbon source added in biofloc system (Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%